2009
DOI: 10.1242/dev.042242
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42- and IRSp53-dependent contractile filopodia tether presumptive lens and retina to coordinate epithelial invagination

Abstract: The vertebrate lens provides an excellent model with which to study the mechanisms required for epithelial invagination. In the mouse, the lens forms from the head surface ectoderm. A domain of ectoderm first thickens to form the lens placode and then invaginates to form the lens pit. The epithelium of the lens placode remains in close apposition to the epithelium of the presumptive retina as these structures undergo a coordinated invagination. Here, we show that F-actin-rich basal filopodia that link adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 83 publications
4
94
0
2
Order By: Relevance
“…In addition to these biochemical interactions, mechanical links may play a role in the coordinated eye development. Another recent report has shown an intriguing connection between lens and neural retinal epithelium, which invaginate at the same time (Chauhan et al, 2009). Close observations of this process reveal that there is a gap between the basement membranes of the two tissues, refuting the idea of mechanical pushing between them.…”
Section: Reconciling In Vitro and In Vivo Datamentioning
confidence: 97%
“…In addition to these biochemical interactions, mechanical links may play a role in the coordinated eye development. Another recent report has shown an intriguing connection between lens and neural retinal epithelium, which invaginate at the same time (Chauhan et al, 2009). Close observations of this process reveal that there is a gap between the basement membranes of the two tissues, refuting the idea of mechanical pushing between them.…”
Section: Reconciling In Vitro and In Vivo Datamentioning
confidence: 97%
“…A different type of constraint may be at work in the vertebrate eye, where two epithelia -the neural retina and the overlying lens placode -invaginate in close apposition to form a cup. In this case, thin actin-myosin-containing cellular protrusions connect the two epithelia during invagination, and disruption of these protrusions results in a reduction in the depth of lens cell invagination (Chauhan et al, 2009). In this case, the out-of-plane bending of one tissue could be mechanically coupled to that of another.…”
Section: Possible Roles For Mechanical Feedback and External Constraintsmentioning
confidence: 99%
“…Because filopodia are thought to be important for angiogenesis (Gerhardt et al, 2003) and Cdc42 has been shown to be necessary for filopodial development (Chauhan et al, 2009;Mattila and Lappalainen, 2008), we assessed sprouting EC filopodia in Cdc42…”
Section: Cdc42 Is Necessary For Endothelial Filopodia and Sproutingmentioning
confidence: 99%